DESIGN ELEMENTS AND RISKS OF CENTRAL BANK DIGITAL CURRENCY IN TAILORING A PRUDENT ‘RUPIAH DIGITAL’ - Wahyu Yun Santoso; Araya Anggara Putra; Laras Susanti; Faiz Rahman (Fakultas Hukum, Universitas Diponegoro, 2023)
Alongside with the increasing of risks associated with the use of stablecoins, Central Bank of Indonesia is considering the issuance of Central Bank Digital Currencies (CBDCs) to mitigate these risks. However, as a manifestation of innovation in financial sector, its characteristic must carefully address potential consequences and risks. Central Bank of Indonesia asserts that a robust legal framework forms the cornerstone of CBDC implementation. This paper aims to examine the legal considerations that could arise during CBDC’s utilization in Indonesia. Given the nascent state of Indonesia's legal framework concerning cyber privacy and security, this paper also explores the privacy and cybersecurity risks correlated with CBDC’s implementation. This research finds indicate that Indonesia's regulatory framework is currently insufficient to support CBDC implementation adequately. The legitimacy of CBDC hinges on whether it is classified as currency or mere payment instruments. Moreover, existing regulations do not fully address privacy concerns, necessitating additional provisions to safeguard retail CBDC users, despite the recent enactment of overarching legislation on Indonesian personal data protection. Regarding cybersecurity, urgent measures are needed to pass a comprehensive Cybersecurity Law, as current provisions do not provide adequate safeguards for CBDC.